Sin*a*gogue : sin and failure in Jewish thought - Bashevkin, David, 1985- (New perspectives in post-Rabbinic Judaism., 2019)
This volume presents the concepts of sin and failure in Jewish thought, weaving together biblical and rabbinic studies to reveal a holistic portrait of the notion of sin and failure within Jewish thought.